Can ammonia tolerance amongst lichen functional groups be explained by physiological responses? (Environmental pollution (Barking, Essex : 1987), 2014)
Ammonia (NH3) empirical critical levels for Europe were re-evaluated in 2009, based mainly on the ecological responses of lichen communities without acknowledging the physiological differences between oligotrophic and nitrophytic species. Here, we compare a nitrogen sensitive lichen (Evernia prunastri) with a nitrogen tolerant one (Xanthoria parietina), focussing on their physiological response (Fv/Fm) to short-term NH3 exposure and their frequency of occurrence along an NH3 field gradient. Both frequency and Fv/Fm of E. prunastri decreased abruptly above 3 μg m(-3) NH3 suggesting direct adverse effects of NH3 on its photosynthetic performance. By contrast, X. parietina increased its frequency with NH3, despite showing decreased capacity of photosystem II above 50 μg m(-3) NH3, suggesting that the ecological success of X. parietina at ammonia-rich sites might be related to indirect effects of increased nitrogen (NH3) availability. These results highlight the need to establish NH3 critical levels based on oligotrophic lichen species.

Tools for determining critical levels of atmospheric ammonia under the influence of multiple disturbances (Environmental Pollution, 2014)
Critical levels (CLEs) of atmospheric ammonia based on biodiversity changes have been mostly calculated using small-scale single-source approaches, to avoid interference by other factors, which also influence biodiversity. Thus, it is questionable whether these CLEs are valid at larger spatial scales, in a multi- disturbances context. To test so, we sampled lichen diversity and ammonia at 80 sites across a region with a complex land-cover including industrial and urban areas. At a regional scale, confounding factors such as industrial pollutants prevailed, masking the CLEs. We propose and use a new tool to calculate CLEs by stratifying ammonia concentrations into classes, and focusing on the highest diversity values. Based on the significant correlations between ammonia and biodiversity, we found the CLE of ammonia for Mediterranean evergreen woodlands to be 0.69 mgm?3, below the previously accepted value of 1.9 mgm?3, and below the currently accepted pan-European CLE of 1.0 mgm?3

Critical loads of nitrogen deposition and critical levels of atmospheric ammonia for semi-natural Mediterranean evergreen woodlands (Biogeosciences, 2012)
Nitrogen (N) has emerged in recent years as a key factor associated with global changes, with impacts on biodiversity, ecosystems functioning and human health. In order to ameliorate the effects of excessive N, safety thresholds such as critical loads (deposition ﬂuxes) and levels (concentrations) can be established. Few studies have assessed these thresholds for semi-natural Mediterranean ecosystems. Our objective was therefore to determine the critical loads of N deposition and long-term critical levels of atmospheric ammonia for semi-natural Mediterranean evergreen woodlands. We have considered changes in epiphytic lichen communities, one of the most sensitive comunity indicators of excessive N in the atmosphere. Based on a classiﬁcation of lichen species according to their tolerance to N we grouped species into response functional groups, which we used as a tool to determine the critical loads and levels. This was done for a Mediterranean climate in evergreen cork-oak woodlands, based on the relation between lichen functional diversity and modelled N deposition for critical loads and measured annual atmospheric ammonia concentrations for critical levels, evaluated downwind from a reduced N source (a cattle barn). Modelling the highly signiﬁcant relationship between lichen functional groups and annual atmospheric ammonia concentration showed the critical level to be below 1.9 µg m−3 , in agreement with recent studies for other ecosystems. Modelling the highly signiﬁcant relationship between lichen functional groups and N deposition showed that the critical load was lower than 26 kg (N) ha−1 yr−1 , which is within the upper range established for other semi-natural ecosystems. Taking into account the high sensitivity of lichen communities to excessive N, these values should aid development of policies to protect Mediterranean woodlands from the initial effects of excessive N.

Lichen functional groups as ecological indicators of the effects of land-use in Mediterranean ecosystems (Ecological Indicators, 2012)
The effects of land-use on species and communities are usually studied by considering high-intensity land-use gradients. However, in many Mediterranean Europe areas, the traditional land-use regime is of low-intensity, including low-impactforestry practices and extensive livestock pasture. This low-intensity land-use is associated with ‘High Nature Value Farmlands’, which occupymore than 50% oftotal farmland area in Mediterranean areas. The objective of this work was to determine the effect of traditional lowintensity land-use on epiphytic lichen communities in Mediterranean cork-oak woodlands. We intend to investigate the value of lichen communities as early indicators of the effects of land-use changes. For that, lichens were sampled along a gradient of low-intensity land-use that included forestry and pasture activities. As lichen diversity variables we considered: (i) total species richness, (ii) total species frequency (LDV), and (iii) richness and frequency of functional groups dividing species according to their eutrophication-tolerance. We found an increase of total species richness with an increase of land-use intensity which is opposite to expectations and which was shown for ﬁrst time in lichens. The increase in total species richness was due to an increase of the number of eutrophication tolerant species accompanied by the maintenance of the sensitive one when we analyzed the lichen-data at the functional response group level. These results ﬁt with the intermediate disturbance hypothesis that predicts higher diversity under an intermediate disturbance due to the coexistence of species with contrasting ecological requirements. Traditionally managed cork-oak woodlands with low-intensity land-use can thus support a high diversity of lichen species. An important outcome was that we conﬁrmed the importance of using ecological indicators based on functional-groups for monitoring changes in ecosystems and, since lichens responded to low levels of land-use intensity, we have also shown the possibility of using lichens as early indicators of the impacts of low intensity land-use.

Causes of change in nitrophytic and oligotrophic lichen species in a Mediterranean climate: impact of land cover and atmospheric pollutants. (Environmental pollution (Barking, Essex : 1987), 2008)
With the aim of determining the main drivers of changes in nitrophytic and oligotrophic macro-lichen communities in an industrial region with a Mediterranean climate, we considered both land-cover types and atmospheric pollutants. We determined the relation between the abundance of nitrophytic and oligotrophic species with environmental factors considering the distance of influence of land-cover types. The results showed that oligotrophic species decreased in the proximity of artificial areas, barren land and agricultural areas, associated with higher concentrations of NO2 and Zn, and Ti, probably dust of industrial and agricultural origin. Nitrophytic species were positively related to all the mentioned land-cover types, and with higher concentrations of Fe and N. Magnesium, probably from ocean aerosols, was negatively related to oligotrophic species and positively to nitrophytic.